Economic fragility of Turkey: Assessment of the 1998-2012 period - Seher Nur Sülkü; Bedriye Saraçoğlu (Turkish Economic Association, 2013)
This study aims to evaluate the vulnerability of the Turkish economy in the context of global crises during the 1998:01-2012:08 period employing signals approach improved by Kaminsky, Lizando and Reinhart (1998) [KLR]. Our study is necessary and timely to assess the fragility of Turkey since the recent crises created a debate on the Turkish economy. We consider more than thirty financial and macroeconomic variables and choose the best performing eighteen variables according to KLR criteria. The real interest rate differential between Turkey and U.S. ranked first according to all the criteria under consideration. Then, we construct composite indices to estimate the probabilities of crises. According to our findings, the probability of a crisis seems very low for Turkey in 2013, as none of the indicators give any signal of a crisis. Even though our study supports the buoyancy of the Turkish economy, it is important to keep monitoring it as global or unexpected developments may create fragilities.
Keywords: F31; F32; F47; H60; 330; Economic Vulnerability; 2008-09 Crisis; Leading Indicators; Signals Approach; Turkey